Strong restructuration of skin microbiota during captivity challenges ex-situ conservation of amphibians - Fieschi-Méric, Léa; Van Leeuwen, Pauline; Hopkins, Kevin; Bournonville, Marie; Denoël, Mathieu; Lesbarrères, David (Frontiers in Microbiology, 2023)
In response to the current worldwide amphibian extinction crisis, conservation instances have encouraged the establishment of ex-situ collections for endangered species. The resulting assurance populations are managed under strict biosecure protocols, often involving artificial cycles of temperature and humidity to induce active and overwintering phases, which likely affect the bacterial symbionts living on the amphibian skin. However, the skin microbiota is an important first line of defense against pathogens that can cause amphibian declines, such as the chytrid Batrachochytrium dendrobatidis (Bd). Determining whether current husbandry practices for assurance populations might deplete amphibians from their symbionts is therefore essential to conservation success. Here, we characterize the effect of the transitions from the wild to captivity, and between aquatic and overwintering phases, on the skin microbiota of two newt species. While our results confirm differential selectivity of skin microbiota between species, they underscore that captivity and phase-shifts similarly affect their community structure. More specifically, the translocation ex-situ is associated with rapid impoverishment, decrease in alpha diversity and strong species turnover of bacterial communities. Shifts between active and overwintering phases also cause changes in the diversity and composition of the microbiota, and on the prevalence of Bd-inhibitory phylotypes. Altogether, our results suggest that current husbandry practices strongly restructure the amphibian skin microbiota. Although it remains to be determined whether these changes are reversible or have deleterious effects on their hosts, we discuss methods to limit microbial diversity loss ex-situ and emphasize the importance of integrating bacterial communities to applied amphibian conservation.